Galen from Pergamon (130-200 years) – Views in ophthalmology. Part II – anatomy description of the eye - Bieganowski, Lech (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The article presents Galen’s views on the anatomy of the eye. He believed that the eye was composed of membranes and fluids. He distinguished the following membranes of the eye: the cornea, the sclera, the choroid, the capsula of the lens and the retina, as well as the structure covering the muscles of the eye and joining the individual elements of the eye with the orbital cavity and the skull (i. e. the bulbar conjunctiva and Tenon’s capsula). The following were considered as fluid substances of the eye: egg – shaped fluid (i. e. albuminous fluid), crystal fluid (i. e. the lens) and vitreous fluid. The article also outlines his theory of vision. It assumes the existence of a specific life force called pneuma which is under a considerable influence of the soul and which reaches the eye from the brain through small channels in the optic nerve. Due to this element the eye was supposed to have the vision ability located in the lens which was the most important part of the eye receiving the vision sensations.